PENANGANAN TUMPAHAN MINYAK TENAGA SURYA MENGGUNAKAN MEDIA LIMBAH KULIT DURIAN - Regil Kentaurus Harryes; Veryawan Nanda Perkasa; Timbul Haryanto Agus Rahmadi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The problem of oil pollution in the sea is starting to get serious attention from the public. This incident caused the mass death of various types of marine organisms. Many cases only become government records without any complete response. An example of a case is oil pollution in Seribu Island. It is known that pollution has occurred since 2003 and in the 2003-2004 period it was recorded that it had occurred 6 times. To prevent and control marine pollution due to oil spills, there are several prevention methods. We know that the case is difficult to do because the oil spill is very done, both in terms of time, continuous work, and in terms of the costs involved. In this study, the design and construction of oil extraction using absorbent media in the oil waste area in the water. The purpose of this research is to design and conduct a study of the efficiency of a belt type oil skimmer using durian skin waste which is moved using a solar panel. It absorbs oil from the air which can be retrieved and collected onto the vessel by providing a piping arrangement. The collected oil can be reused for various purposes.